Gambaran Kadar Serum Glutamic Pyruvic Transaminase (SGPT) pada Penderita Demam Tifoid - Rahmawati Rahmawati; Muawanah Muawanah; Dewi Arisanti; Fira Al Munawwarah; Wa Ode Rustiah (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2023)
Typhoid fever is an acute systemic disease caused by the bacterium Salmonella typhi. Salmonella typhi found in the small intestine will multiply and then produce endotoxin, where the endotoxin produced is a lipopolysaccharide complex and is considered to play a key role in the pathogenesis of typhoid fever. If it enters the body, it will cause the body's condition to become weak, making it easier for Salmonella typhi bacteria to attack body tissues such as the liver and cause SGPT levels to increase. Liver damage in patients with typhoid fever in the form of changes in hepatomegaly, jaundice, biochemical, and histopathological changes. This study aims to provide an overview of Serum Glutamic Pyruvic Transaminase (SGPT) levels in patients with typhoid fever at Haji General Hospital, Makassar City. The method in this study was descriptive, with a sample population of 10 typhoid fever patients. The sampling technique used is Random Sampling. From a study conducted on 10 samples of typhoid fever patients, it was found that 6 samples had normal SGPT levels, and 4 samples had high SGPT levels, with the highest level being 95.2 µl and the lowest level being 15.9 µl. It can be concluded that the increased levels of SGPT in patients with typhoid fever is due to strenuous physical activity and taking certain drugs which can trigger increased levels of SGPT.